2008
DOI: 10.1007/s00270-008-9419-0
|View full text |Cite
|
Sign up to set email alerts
|

Restenosis After Balloon Angioplasty for Cerebral Vasospasm

Abstract: Transluminal balloon dilatation for symptomatic vasospasm after subarachnoid hemorrhage is effective, and clinical studies have shown that it achieves long-lasting dilatation of spastic cerebral arteries. Delayed arterial renarrowing has not been reported. Here we report the case of a 58-year-old woman who presented asymptomatic and permanent restenosis after angioplasty for cerebral vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Although the specific mechanism of action responsible for the effects of TBA are not well understood, several are likely to be at play, including but probably not limited to disruption or dysfunction of smooth muscle cells, extracellular matrix, or connections between the basement membranes of the cells. 30,39,48 Although it has been shown that TBA causes smooth muscle and endothelial cell flattening, some extracellular matrix disruption, and denudation of the endothelial lining, TBA is not thought to cause major irreversible structural damage. 29,30 These mechanisms usually result in a robust patency after angioplasty, with resilience to further spasm, but it should be noted that these vessels may also become less responsive to pharmacological vasodilators.…”
Section: Intraarterial Vasodilatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the specific mechanism of action responsible for the effects of TBA are not well understood, several are likely to be at play, including but probably not limited to disruption or dysfunction of smooth muscle cells, extracellular matrix, or connections between the basement membranes of the cells. 30,39,48 Although it has been shown that TBA causes smooth muscle and endothelial cell flattening, some extracellular matrix disruption, and denudation of the endothelial lining, TBA is not thought to cause major irreversible structural damage. 29,30 These mechanisms usually result in a robust patency after angioplasty, with resilience to further spasm, but it should be noted that these vessels may also become less responsive to pharmacological vasodilators.…”
Section: Intraarterial Vasodilatorsmentioning
confidence: 99%
“…10,18,23,36,39,43,48 The most feared complication is vessel rupture, which can occur when there is discordant balloon diameter to vessel size. Occasionally, in the absence of a prespasm baseline angiographic study, the "normal" size of a spastic vessel must be estimated based on anatomical assumptions.…”
Section: Intraarterial Vasodilatorsmentioning
confidence: 99%
“…In a review by Hoh and Ogilvy [74], balloon angioplasty had an approximately 5% risk of major complication, including an approximate 1% risk of vessel perforation/rupture, which is usually fatal [17,18,63,71,72,73,74,75,76]. Recently, some authors described the occurrence of delayed stenosis after angioplasty [77,78]. Although uncommon, recurrence of vasospasm after angioplasty may also occur [79].…”
Section: Endovascular Therapy In Sah-induced Cerebral Vasospasmmentioning
confidence: 99%
“…Restenosis after balloon angioplasty for atherosclerosis is a well-known phenomenon [9][10][11], however, its occurrence in a delayed fashion following its use for cerebral vasospasm is rare [12][13][14]. We report a patient who underwent successful angioplasty for internal carotid artery (ICA) post-SAH vasospasm, who went on to develop delayed progressive severe focal restenosis.…”
Section: Introductionmentioning
confidence: 98%